Efficacy of buffered and enteric-coated acetylsalicylic acid on platelet aggregation in patients with stable coronary artery disease and type 2 diabetes (CASCADE): rationale and design of a single-center observational comparative study - Zh. D. Kobalava; A. S. Pisaryuk; A. A. Filkova; E. S. Tukhsanboev; A. N. Amirova; A. D. Korneichuk; G. S. Pavlikov; L. R. Burkhanova; I. A. Meray; M. A. Panteleev; A. N. Sveshnikova (Российский кардиологический журнал)
Aim. Enteric-coated acetylsalicylic acid (ASA) is released more slowly and is absorbed in smaller quantities and over a longer period of time, which may lead to bioavailability and antiplatelet effect decrease compared to conventional ASA. Patients with diabetes are characterized by increased platelet reactivity and a reduced pharmacodynamic response to ASA compared to individuals without diabetes. It seems rational to test the hypothesis that the use of ASA absorbed in the stomach may be more effective in patients with type 2 diabetes mellitus (T2D) and stable coronary artery disease (CAD).Material and methods. This single-center, non-interventional comparative study will randomly select 200 adult patients of both sexes with stable CAD and T2D who were routinely prescribed a gastro-soluble ASA (Cardiomagnyl 75 mg/day) or an enteric-soluble ASA (Aspirin® Cardio 100 mg/day or Thrombo ASS® 100 mg/day) before inclusion in the study. According to the routinely prescribed therapy, patients will be divided into 2 following groups: patients taking Cardiomagnyl 75 mg/day and patients taking Aspirin® Cardio 100 mg/day or Thrombo ASS® 100 mg/day. The primary endpoint is the incidence of high residual platelet reactivity (HRPR) while taking ASA (resistance to ASA) according to the VerifyNow Aspirin Test.Conclusion. CASCADE is the first study to evaluate the HRPR using the VerifyNow Aspirin Test in patients with stable CAD and T2D.